1994
DOI: 10.1177/107110079401500508
|View full text |Cite
|
Sign up to set email alerts
|

The Plantar Plate of the Lesser Toes: An Anatomical Study in Human Cadavers

Abstract: The purpose of this study was to evaluate the anatomic structure and biochemical composition of the plantar plate of the lesser toes. Fresh frozen-human cadaveric feet were used to study 20 metatarsophalangeal and proximal interphalangeal plantar plates. The observations of foot dissections were compared with the finger volar plate. The plantar plate of the toe is a rectangular structure with a stout distal insertion and relatively flimsy proximal origin. The anatomic relationships to adjacent structures and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 11 publications
1
106
1
4
Order By: Relevance
“…Furthermore, collateral ligament injury undermined the role of the PP in this setting. Johnston et al 12 reported on the anatomical and histological composition of the PP compared to the volar plate. They described the weak proximal attachment of the PP and stipulated that it could aid in dorsiflexion of the proximal phalanx over the metatarsal head.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, collateral ligament injury undermined the role of the PP in this setting. Johnston et al 12 reported on the anatomical and histological composition of the PP compared to the volar plate. They described the weak proximal attachment of the PP and stipulated that it could aid in dorsiflexion of the proximal phalanx over the metatarsal head.…”
Section: Discussionmentioning
confidence: 99%
“…This plate, formed by the plantar aponeurosis and the plantar joint capsule, plays a major role in dorsoplantar stability of the MTP joint (Bhatia et al 1994, Johnston et al 1994. Once the plate deteriorates, there are no major antagonists for the extensors, and the proximal phalanx is inevitably pulled dorsally out of the joint.…”
mentioning
confidence: 99%
“…This thick plate supports the undersurface of the metatarsal head and resists hyperextension of the MTP joint. It is a flexible fibrocartilage structure that is mainly composed of collagen type I (about 75%) (Sarrafian, 1993;Johnston et al, 1994). All MR images were normal except for the absence of the medial sesamoid (Fig.…”
Section: Case Reportmentioning
confidence: 96%